Minangkabau Women Balance the Role of a Mother and Entrepreneur in the Cultural System They Profess - Fitria Sari; Sapriya Sapriya; Nana Supriatna; Hari Mulyadi; Asnimawati Asnimawati (Aulad)
Minangkabau women, known as Bundo Kanduang, play a crucial role in raising children while also managing businesses. As societal dynamics evolve, they face the challenge of balancing their roles as mothers and entrepreneurs. This study aims to analyze how Minangkabau women navigate these dual roles within their cultural system and to identify the parenting values they uphold. A qualitative research approach was employed using ethnographic methods based on Spradley’s research framework. The study involved 10 informants from Dharmasraya Regency, West Sumatra. Data analysis was conducted through domain, taxonomic, and component analysis, with data validity ensured through source, technique, and time triangulation. Findings reveal that Minangkabau women’s parenting emphasizes ten core values, including independence, honesty, creativity, and solidarity, which significantly contribute to shaping children's character in adapting to modern challenges.